2019
DOI: 10.1016/j.euo.2018.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Mannose Receptor–positive Macrophage Infiltration Correlates with Prostate Cancer Onset and Metastatic Castration-resistant Disease

Abstract: Background: M2 tumor-associated macrophages (M2-TAMs) can suppress inflammation in the tumor microenvironment and have been reported to modulate cancer progression. We and others have previously reported M2-TAM infiltration in metastatic castration-resistant prostate cancer (mCRPC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 29 publications
7
59
1
Order By: Relevance
“…63 In addition, tumor-associated macrophages (TAMs) are an important component of tumor microenvironment. Recently Zarif et al 64 showed that TAM can reprogram tumor phenotype and play a major role in the emergence of a neuroendocrine phenotype in prostate cancers. Targeting these signals in the prostate cancer microenvironment could potentially augment immunotherapeutic approaches in NEPC.…”
Section: Lineage Plasticity Driving Development Of Nepcmentioning
confidence: 99%
“…63 In addition, tumor-associated macrophages (TAMs) are an important component of tumor microenvironment. Recently Zarif et al 64 showed that TAM can reprogram tumor phenotype and play a major role in the emergence of a neuroendocrine phenotype in prostate cancers. Targeting these signals in the prostate cancer microenvironment could potentially augment immunotherapeutic approaches in NEPC.…”
Section: Lineage Plasticity Driving Development Of Nepcmentioning
confidence: 99%
“…Macrophages positive for CD206, a biomarker for the M2/TAM macrophage phenotype, 12,42 were observed in rat prostates showing early proliferative lesions, even before malignancy was established. Similar findings have been reported previously in breast tissue 43 and the prostate 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells and M2-like macrophages occupy a substantial part of the tumor habitat and have marked influence on the tumor ecosystem as a whole. [30][31][32] Cancer cells and macrophages support each other by secreting factors that stimulate the others' growth, survival, and, importantly, support tumorpromoting ecosystem engineering (Figure 2A). The ecosystem engineering of the cancer cells, the primary invader population, recruits secondary invasion of M2 macrophages by releasing cytokines that recruit and polarize M2 macrophages.…”
Section: Cooperative Invasive Ecosystem Engineersmentioning
confidence: 99%